LANDSCAPE GENRE AND ITS DISTINCTIVE FEATURES IN FINE ART (British Journal of Global Ecology and Sustainable Development, 2024)
The world consists of endless mysteries. It can be symbolically likened to the "Black Square" of a bamisoli musician. After all, the literary creation of the "square" means the symbol of generosity on four sides, and the "black" indicates that subjectivity is an incomprehensible mystery of all the mysteries of the world. No matter how many secrets mankind tries to learn, it is only natural for its thinking to be vulnerable. In pirovardi, you come to the philosophical conclusion that it takes a person unlimited life to learn these miracles, man.